The essential role of TAp73 in bortezomib-induced apoptosis in p53-deficient colorectal cancer cells - Dabiri, Yasamin; Mayer, Viola; Cheng, Xinlai (Scientific reports, 2017)
Mutations in the tumor suppressor p53 are among the most highly occurring events in colorectal cancer (CRC). Such mutations have been shown to influence the sensitivity of cancer cells to chemotherapeutic agents. However their impact on the efficacy of the proteasomal inhibitor bortezomib remains controversial. We thus re-evaluated the toxicity of bortezomib in the CRC cell lines HCT116 wt (wild-type) and its p53−/− clone. Transient resistance to bortezomib treatment was observed in p53-null cells that was later accompanied by an increase in levels and nuclear translocation of TAp73, an isoform of the p53-homologue p73, as well as induction of apoptosis. Knockdown of p73 in p53−/− cells using CRISPR/Cas9 significantly prolonged the duration of resistance. Moreover, similar results were observed in HT-29 cells carrying mutated p53, but not human fibroblasts with expression of functional p53. Thus, our results clearly demonstrated that TAp73 served as a substitute for p53 in bortezomib-induced apoptosis in p53-deficient or mutated cells, implicating that TAp73 could be a potential therapeutic target for treatment of CRCs, in particular those lacking functional p53.